2009
DOI: 10.1002/adsc.200900434
|View full text |Cite
|
Sign up to set email alerts
|

Tandem Enzyme/Gold‐Catalysis: From Racemic α‐Allenic Acetates to Enantiomerically Enriched 2,5‐Dihydrofurans in One Pot

Abstract: Abstract:We report the first example of a tandem kinetic resolution/cycloisomerization of racemic allenic acetates in the presence of Burkholderia cepacia lipase (PS Amano SD) and catalytic amounts of chloroauric acid (HAuCl 4 ) which affords 2,5-dihydrofurans, as well as unreacted starting material, in one pot with high enantiomeric excess and moderate to good yield.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
29
0
2

Year Published

2010
2010
2015
2015

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 72 publications
(31 citation statements)
references
References 25 publications
0
29
0
2
Order By: Relevance
“…[20] This research group has also presented a binary catalytic system that consists of an enzyme and a gold complex and yields 2,5-dihydrofurans from racemic a-allenic acetates. [21] With regard to synthetic efficiency, this result is a leap forward from the previously published sequential transformations. [22] …”
mentioning
confidence: 87%
“…[20] This research group has also presented a binary catalytic system that consists of an enzyme and a gold complex and yields 2,5-dihydrofurans from racemic a-allenic acetates. [21] With regard to synthetic efficiency, this result is a leap forward from the previously published sequential transformations. [22] …”
mentioning
confidence: 87%
“…We were delighted to observe a smooth formation of the desired 2,5-dihydrofurans 4 from substrate 1a and arylboronic acids bearing different substituents in the o-, m-and p-positions (Table 3, entries 1-14), a thiophene ring (Table 3, entry 15), or a 2-naphthyl group (Table 3, entry 16). The one-pot process tolerates both electron-rich (Table 3, entries 2, 6,7,8,12,13) and electron-deficient aryl groups (Table 3, entries 3, 4, 5, 9, 10, 11, 14). The chemical yields were high in most cases.…”
Section: Resultsmentioning
confidence: 99%
“…[1] Whereas numerous tandem or one-pot processes involving traditional transition metal catalysts (in particular palladium) have been reported, [2] there is only a limited number of combinations of gold catalysis (which may be the most intensely used transition metal at present [3] ) with other metal catalysts, [4] organocatalysts, [5] or enzymes. [6] So far, only three reports describing the combination of gold with another transition metal catalyst in a tandem or one-pot sequence have appeared. [7] Uemura et al [4a] reported a one-pot synthesis of oxazoles from propargylic alcohols and amides in the presence of a ruthenium catalyst and AuCl 3 whereas Akai and co-workers [4b] used the combination of MoO 2 A C H T U N G T R E N N U N G (acac) 2 , Ph 3 PAuCl, and AgOTf to induce a 1,3-rearrangement of propargylic alcohols to a,b-unsaturated carbonyl compounds.…”
Section: Introductionmentioning
confidence: 99%
“…We have utilized this system for the first example of a tandem lipase/ gold-catalyzed transformation. The one-pot kinetic resolution/ cycloisomerization of racemic allenic acetates (AE)-22 with Burkholderia cepacia lipase (PS Amano SD) and HAuCl 4 afforded 2,5-dihydrofurans (R)-23, as well as unreacted starting material (S)-22, with 28e50% isolated yield and 86e98% ee (Scheme 11) [31]. The mutual tolerance of the Lewis-acidic gold catalyst with the Lewis-basic lipase is maintained as long as low amounts of the former are used.…”
Section: Improvement Of Efficiency and Sustainabilitymentioning
confidence: 99%